PENANGANAN PERMUKIMAN KUMUH DI KELURAHAN TEGAL SARI III KECAMATAN MEDAN AREA KOTA MEDAN - Maymaran, Atma; Sembiring, Rahmad Dian; Pinem, Dessy Eresina (LPPM ISTP, 2024)
Slum settlements are a problem faced by almost all cities in Indonesia and other developing countries. This problem is a major obstacle to city development. Rapid population growth, inadequate physical, socio-cultural and economic conditions have resulted in the growth of slum settlements. Slum conditions are known in terms of poor building conditions, roads and drainage as well as poor waste systems. Medan Area District is a district that has been identified as having a slum area. Based on data sources from the Regional Development Planning Agency (BAPPEDA), Tegal Sari III Village in Medan District, the area is included in the slum settlements of Medan City. Then research was carried out on slum settlements with the objectives to be achieved, namely: Analyze the level of slums in Tegal Sari III Village based on parameters. Plan a pattern for handling slum settlements in Tegal Sari III Village. To obtain results for this purpose, the analysis carried out in this research is a weighting analysis, so the results of this research are the level of slums and the results of the handling patterns come out.